ETHICS AND THE BIBLE: Insights from Lonergan, McEvenue, and Meyer - Melchin, Kenneth (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2023)
This article draws on works by Bernard Lonergan, Sean McEvenue, and Ben Meyer to propose a research approach to the topic of bible and ethics. The article begins with a discussion of religious meaning. Two core ideas, rooted in an understanding of religious meaning, are developed to guide the research: “transformative experience” and “sublation.” Two illustrations of this approach are offered with discussions of texts by McEvenue and Meyer.